Between querellae and the ars: sketches of a rhetoric of seduction in Ovid’s Heroide 15 (Argos, 2024)
The authenticity of Ovid’s Heroide 15 (Sappho Phaoni) has triggered muchcritical controversy. In its light, I revisit Sappho’s letter to show some narrative,intratextual and stylistic strategies that reveal its transitional role between the othersingle (1-15) and double (16-21) elegies. I focus on two major points: I examine towhat extent this Heroide features as a “proem in the middle” that governs thewhole collection; and I draw attention on how its inscription in the elegiacdiscourse anticipates some aspects of Ovid’s Ars and thus demarcates some keyissues of his literary writing.
Keywords: Ovid; Heroides; Sappho; Proem in the middle; Intratextuality